Born behind bars - Venkatraman, Padma, 1969- (Nancy Paulsen Books, 2021)
In Chennai, India, after spending his whole life in jail with his mother, who is serving time for a crime she did not commit, nine-year-old Kabir is suddenly released and has to figure out how to survive on his own in the outside world.